Phosphate-based positive electrode material, preparation method and application thereof

CN120637426BActive Publication Date: 2026-10-09SHENZHEN DYNANONIC CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510734310.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2026-10-09
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

然而,受限于现行固相法生产工艺,实现一次颗粒比例的精准调控以匹配设计要求仍面临显著挑战

Benefits of technology

[0015] The first aspect of this application provides a phosphate-based cathode material comprising core-shell structured composite particles. The raw materials for the phosphate-based cathode material include a specific lithium source, a specific iron source, and an iron-based dispersant. Due to the high decomposition temperature of lithium carbonate, the reaction crystallization time when it forms lithium-containing salts with iron phosphate is broad, providing conditions for forming primary particles with larger particle sizes. The iron-based dispersant can form complexes with iron ions, thereby adjusting the particle size of the primary particles through its steric hindrance or charge repulsion effect. The two work synergistically to give the composite particles a suitable particle size distribution: primary particles with a particle size in the range of 150 nm to 2000 nm account for no less than 80% of the total. This moderate particle size distribution endows phosphate-based cathode materials with multiple performance advantages: First, moderate particle size distribution can significantly shorten the lithium-ion diffusion path, reduce interfacial impedance, and effectively improve the rate performance of the material; second, reasonable particle size distribution can increase the compaction density of the electrode, thereby increasing the energy density of the battery; third, uniform particle size distribution makes the stress distribution of the cathode material more uniform during charging and discharging, greatly alleviating volume expansion, reducing the risk of particle breakage, enhancing the structural stability of the material, and significantly improving the cycle performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637426B_ABST
    Figure CN120637426B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of battery materials, and provides a phosphate-based positive electrode material and a preparation method and application thereof. The phosphate-based positive electrode material provided by the application comprises a plurality of composite particles, and the composite particles comprise a lithium-containing phosphate inner core and a carbon shell layer; in the composite particles, the number ratio of primary particles with a particle size of 150 nm-2000 nm is not less than 80%; raw materials of the phosphate-based positive electrode material comprise a lithium source, an iron source and an iron-based dispersant; wherein the lithium source comprises lithium carbonate; the iron source comprises iron phosphate; and the iron-based dispersant comprises an iron-multiple amine complex. The phosphate-based positive electrode material provided by the application has appropriate particle grading, can not only significantly shorten a lithium ion diffusion path, reduce an interface impedance and effectively improve the rate performance of a battery, but also can improve the compaction density of a pole piece, and further improve the energy density of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery materials technology, and in particular relates to a phosphate-based cathode material, its preparation method and application. Background Technology

[0002] Lithium-ion batteries have distinguished themselves in the rechargeable battery field due to their advantages such as high operating voltage, high energy density, and long cycle life. Among them, lithium iron phosphate, as the cathode material of lithium-ion batteries, is regarded as an ideal choice for promoting the large-scale development of the new energy industry due to its advantages such as high capacity, long cycle life, good stability, environmental friendliness, and low cost.

[0003] Currently, lithium iron phosphate (LFP) plays a crucial role as a cathode material in both power batteries and energy storage batteries. The two types of batteries have different performance requirements: power batteries prioritize energy density, power density, and safety to meet the needs of device range, charge / discharge efficiency, and operational safety; while energy storage batteries focus on battery capacity and cycle life as core indicators, pursuing long-term stable energy storage and release. Since the performance of cathode materials is closely related to key characteristics such as the size of the primary particles, carbon coating process, and metal doping, research on particle distribution has become a hot topic in the industry. However, limited by current solid-state production processes, achieving precise control of the primary particle ratio to match design requirements still faces significant challenges. Summary of the Invention

[0004] The purpose of this application is to provide a phosphate-based cathode material, its preparation method, and its application, aiming to improve the ability to precisely control the particle size and proportion of primary particles in the cathode material, thereby optimizing the performance of the cathode material.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0006] In a first aspect, this application provides a phosphate-based cathode material, comprising a plurality of composite particles, wherein the composite particles comprise a lithium phosphate core and a carbon shell coating the outer surface of the lithium phosphate core;

[0007] In the composite particles, the proportion of primary particles with a particle size of 150nm-2000nm is not less than 80%.

[0008] The raw materials for the phosphate-based cathode material include a lithium source, an iron source, and an iron-based dispersant.

[0009] The lithium source includes lithium carbonate, and the mass percentage of lithium carbonate in the lithium source is not less than 80%; the iron source includes iron phosphate, and the mass percentage of iron phosphate in the iron source is not less than 80%; the iron-based dispersant includes an iron-polyamine complex.

[0010] Secondly, this application provides a method for preparing a phosphate-based cathode material, comprising the following steps:

[0011] The raw material components, including lithium source, iron source, phosphorus source and doping source, are obtained according to the stoichiometric ratio of lithium phosphate. The lithium source includes lithium carbonate and the iron source includes iron phosphate.

[0012] The raw material components, carbon source, iron-based dispersant, and solvent are mixed to obtain a mixture.

[0013] The mixture is sintered to form a phosphate-based cathode material containing a lithium phosphate core and a carbon shell covering the outer surface of the lithium phosphate core.

[0014] Thirdly, this application provides a lithium-ion battery, including a positive electrode and a negative electrode. The positive electrode comprises the phosphate-based positive electrode material provided in the first aspect or the phosphate-based positive electrode material prepared by the preparation method provided in the second aspect.

[0015] The first aspect of this application provides a phosphate-based cathode material comprising core-shell structured composite particles. The raw materials for the phosphate-based cathode material include a specific lithium source, a specific iron source, and an iron-based dispersant. Due to the high decomposition temperature of lithium carbonate, the reaction crystallization time when it forms lithium-containing salts with iron phosphate is broad, providing conditions for forming primary particles with larger particle sizes. The iron-based dispersant can form complexes with iron ions, thereby adjusting the particle size of the primary particles through its steric hindrance or charge repulsion effect. The two work synergistically to give the composite particles a suitable particle size distribution: primary particles with a particle size in the range of 150 nm to 2000 nm account for no less than 80% of the total. This moderate particle size distribution endows phosphate-based cathode materials with multiple performance advantages: First, moderate particle size distribution can significantly shorten the lithium-ion diffusion path, reduce interfacial impedance, and effectively improve the rate performance of the material; second, reasonable particle size distribution can increase the compaction density of the electrode, thereby increasing the energy density of the battery; third, uniform particle size distribution makes the stress distribution of the cathode material more uniform during charging and discharging, greatly alleviating volume expansion, reducing the risk of particle breakage, enhancing the structural stability of the material, and significantly improving the cycle performance and service life of the battery.

[0016] The method for preparing phosphate-based cathode materials provided in the second aspect of this application involves mixing the raw material components, carbon source, and iron-based dispersant to achieve uniform mixing. During sintering, the iron-based dispersant weakens the interparticle attraction through steric hindrance or charge repulsion, thereby inhibiting primary particle agglomeration and controlling the particle size of primary particles in the composite particles. This results in composite particles with a core-shell structure and reasonable particle size distribution, effectively producing the phosphate-based cathode materials with the properties described above. Furthermore, the method for preparing phosphate-based cathode materials in this application is advantageous for obtaining phosphate-based cathode materials with high conductivity and good electrochemical performance. This method is also simple and suitable for industrial-scale mass production.

[0017] The lithium-ion battery provided in the third aspect of this application contains the phosphate-based cathode material of this application, which has the characteristics of moderate particle size distribution, high ionic conductivity, and high electronic conductivity. Therefore, it effectively improves the energy density, rate performance, cycle life and other electrochemical performance of the lithium-ion battery. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a SEM image of the phosphate-based cathode material provided in Example 1 of this application;

[0020] Figure 2 This is a SEM image of the phosphate-based cathode material provided in Comparative Example 1 of this application. Detailed Implementation

[0021] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0022] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0023] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0024] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0025] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0026] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.

[0027] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0028] The first aspect of this application provides a phosphate-based cathode material, comprising a plurality of composite particles. Specifically, the composite particles include a lithium-containing phosphate core and a carbon shell coating the outer surface of the lithium-containing phosphate core, and the proportion of primary particles with a diameter of 150 nm-2000 nm in the composite particles is not less than 80%. The raw materials for the phosphate-based cathode material include a lithium source, an iron source, and an iron-based dispersant; the lithium source includes lithium carbonate, with a mass proportion of lithium carbonate in the lithium source not less than 80%; the iron source includes iron phosphate, with a mass proportion of iron phosphate in the iron source not less than 80%; the iron-based dispersant includes an iron-polyamine complex.

[0029] In the technical solution of this application, lithium carbonate has a high decomposition temperature, decomposing into lithium oxide and carbon dioxide at around 700℃, as shown in chemical reaction formula (I). The decomposition temperature of iron phosphate is also relatively high. This means that the decomposition product of lithium carbonate, lithium oxide, can react with iron phosphate at high temperatures to form lithium-containing phosphates. In other words, during the formation of phosphate-based cathode materials, the reaction crystallization temperature range of lithium carbonate and iron phosphate is wide, allowing crystallization to occur at different temperatures and reaction times, thus contributing to obtaining primary particles with a particle size in the range of 150nm-2000nm.

[0030] Li₂CO₃→Li₂O+CO₂(I)

[0031] The polyamine ligands contained in iron-based dispersants can form complexes with iron ions. These complexes, on the one hand, utilize their own steric hindrance or charge repulsion to adjust the particle size of primary particles; on the other hand, they can form lithium iron phosphate crystal carriers (i.e. lithium phosphate) with lithium sources during subsequent sintering, thereby improving the reactivity of phosphate-based cathode materials.

[0032] Specifically, the iron-based dispersant includes at least one of tri(ethylenediamine)fer(III) nitrate ([Fe(en)3](NO3)3), triethanolaminefer(III) nitrate ([Fe(TEA)](NO3)3), triethylenetetraminefer(III) nitrate ([Fe(TETA)](NO3)3), and ethylenediaminetetraacetic acidfer(III) nitrate ([Fe(EDTA)](NO3)3).

[0033] Based on the synergistic effect between the lithium source, iron source, and iron-based dispersant, the particle size of primary particles in phosphate-based cathode materials can be effectively controlled. Furthermore, by controlling the mass ratio of lithium carbonate and iron phosphate, a reasonable particle size distribution is achieved: primary particles with a diameter in the range of 150nm-2000nm account for no less than 80% of the total. This moderate particle size distribution endows phosphate-based cathode materials with multiple performance advantages: First, the moderate particle size distribution can significantly shorten the lithium-ion diffusion path, reduce interfacial impedance, and effectively improve the rate performance of the material; second, the reasonable particle size distribution can increase the compaction density of the electrode, thereby increasing the energy density of the battery; third, the uniform particle size distribution makes the stress distribution of the cathode material more uniform during charging and discharging, greatly alleviating volume expansion, reducing the risk of particle breakage, enhancing the structural stability of the material, and significantly improving the cycle performance and service life of the battery.

[0034] In addition, the composite particles have a core-shell structure, including a lithium phosphate core and a carbon shell. The carbon shell can effectively improve the conductivity of phosphate-based cathode materials and reduce the interfacial resistance of phosphate-based cathode materials, which plays a significant positive role in improving the stability of phosphate-based cathode materials and improving the electrochemical performance of batteries.

[0035] In one embodiment, the primary particles in the composite particles all have a particle size in the range of 150nm-2000nm, meaning that the proportion of primary particles in this size range is 100%. In another embodiment, the composite particles include not only primary particles with a particle size in the 150nm-2000nm range but also primary particles with a particle size less than 150nm. In this case, the proportion of primary particles with a particle size of 150nm-2000nm is greater than or equal to 80% and less than 100%. In yet another embodiment, the composite particles include not only primary particles with a particle size in the 150nm-2000nm range but also primary particles with a particle size less than 150nm and primary particles with a particle size greater than 2000nm. In this case, the proportion of primary particles with a particle size of 150nm-2000nm is greater than or equal to 80% and less than 100%.

[0036] As an example, in composite particles, the particle size of the primary particles can be any one of 150nm, 200nm, 300nm, 500nm, 700nm, 900nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm, etc., or within any range of two.

[0037] As an example, the proportion of primary particles with a diameter of 150nm-2000nm can be typical but not limiting values ​​such as 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100%.

[0038] As an example, the mass percentage of lithium carbonate in the lithium source can be typical but not limiting values ​​such as 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, and 100%.

[0039] As an example, the mass percentage of iron phosphate in the iron source can be typical but not limiting values ​​such as 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, 100%.

[0040] In some embodiments, the proportion of primary particles with a diameter of 150nm-500nm in the composite particles is not less than 80%.

[0041] As an example, the particle size of a primary particle can be any one of 150nm, 200nm, 25nm, 300nm, 350nm, 400nm, 450nm, 500nm, or within any range of two.

[0042] As an example, in composite particles, the proportion of primary particles with a diameter of 150nm-500nm can be typical but not limiting values ​​such as 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, and 100%.

[0043] By controlling the particle size and proportion of primary particles in the composite particles within the above range, it helps to promote the stacking between primary particles, so that small particles fill the gaps formed by adjacent large particles, forming a more compact stacked structure. This not only helps to improve the compaction density of the electrode, but also optimizes the lithium-ion diffusion path, enabling the battery to exhibit higher energy density and better cycle performance.

[0044] In some embodiments, the molecular formula of the lithium phosphate core is LiFe. 1-x M x PO4, wherein M includes at least one of Ti, Mg, Al, and V, and 0 ≤ x ≤ 0.1.

[0045] As an example, the lithium phosphate core can be at least one of lithium iron phosphate, lithium magnesium iron phosphate, lithium aluminum iron phosphate, lithium titanium iron phosphate, and lithium vanadium iron phosphate.

[0046] In some embodiments, the particle morphology of the phosphate-based cathode material is quasi-spherical.

[0047] The uniform surface curvature of spherical particles shortens the diffusion path of lithium ions within the particles, reduces electron conduction resistance, and improves the rate performance of the cathode material. Furthermore, the relatively uniform contact area between spherical particles and the electrolyte reduces side reactions between the active material and the electrolyte (such as increased interfacial impedance), thus extending battery life.

[0048] In some embodiments, the carbon shell in the phosphate-based cathode material accounts for 1%-10% of the total mass.

[0049] For example, the mass percentage of the carbon shell can be typical but not limiting values ​​such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0050] The fact that the mass percentage of the carbon shell is within the above range means that the carbon shell has an appropriate thickness, which not only achieves the coating of the lithium phosphate core, but also keeps the lithium ions within a suitable migration path range, giving the cathode material high ionic and electronic conductivity, thereby helping to improve the rate performance of the battery.

[0051] In some embodiments, the carbon shell comprises the carbonized product of the ligand in the iron-polyamine complex.

[0052] Polyamines, acting as ligands in the complex, can form complexes with iron ions, thereby controlling the particle size of the primary particles. During subsequent sintering, these ligands undergo carbonization to transform into carbon materials, becoming part of the carbon shell.

[0053] In some embodiments, the 0.1C discharge capacity of the phosphate-based cathode material is greater than or equal to 158 mAh / g.

[0054] In some embodiments, the 0.1C discharge capacity of the phosphate-based cathode material is 158 mAh / g-162 mAh / g.

[0055] The 0.1C discharge capacity of phosphate-based cathode materials falls within the aforementioned range, indicating that they possess high intrinsic capacity. This demonstrates that by limiting the particle size range and proportion of primary particles in phosphate-based cathode materials—specifically, ensuring that the proportion of primary particles with a diameter of 150nm-2000nm is not less than 80%—the lithium-ion transport path is significantly shortened, and the lithium-ion migration rate is increased. This endows the cathode material with higher lithium insertion / extraction efficiency, resulting in higher discharge capacity and thus contributing to improved battery energy density.

[0056] In some embodiments, the 1C discharge capacity of the phosphate-based cathode material is greater than or equal to 148 mAh / g.

[0057] In some embodiments, the 1C discharge capacity of the phosphate-based cathode material is 148 mAh / g-158 mAh / g.

[0058] The 1C discharge capacity of phosphate-based cathode materials falls within the aforementioned range. This indicates that by limiting the particle size range and the proportion of primary particles in the composite particles, specifically, the proportion of primary particles with a particle size of 150nm-2000nm is not less than 80%, the lithium-ion diffusion capacity and electron conduction rate of the cathode material can be effectively improved, thereby enabling the battery to exhibit a higher discharge capacity and showing significant advantages in medium-to-high rate scenarios.

[0059] The second aspect of this application provides a method for preparing a phosphate-based cathode material, comprising the following steps:

[0060] Step S10: Obtain raw material components including lithium source, iron source, phosphorus source and doping source according to the stoichiometric ratio in lithium phosphate. The lithium source includes lithium carbonate and the iron source includes iron phosphate.

[0061] Step S20: Mix the raw material components with the carbon source, iron-based dispersant and solvent to obtain a mixture.

[0062] Step S30: The mixture is sintered to form a phosphate-based cathode material containing a lithium phosphate core and a carbon shell coating the outer surface of the lithium phosphate core.

[0063] The method for preparing phosphate-based cathode materials provided in the second aspect of this application involves mixing the raw material components, carbon source, and iron-based dispersant to ensure uniform mixing. During sintering, the high decomposition temperature of lithium carbonate allows lithium carbonate and iron phosphate to form lithium-containing phosphates at higher temperatures, which helps to form larger primary particles. Furthermore, the iron-based dispersant weakens the interparticle attraction through steric hindrance or charge repulsion, inhibiting primary particle agglomeration and controlling the particle size. This results in composite particles with a core-shell structure and reasonable particle size distribution, effectively producing the phosphate-based cathode material exhibiting the properties described above. Additionally, this method facilitates the production of phosphate-based cathode materials with high conductivity and good electrochemical performance. Moreover, the process is simple and suitable for industrial-scale mass production.

[0064] In some embodiments, in step S10, the lithium source includes lithium carbonate, and the mass percentage of lithium carbonate in the lithium source is 80%-90%.

[0065] As an example, the mass percentage of lithium carbonate in the lithium source can be typical but not limiting values ​​such as 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%.

[0066] Lithium carbonate has a high decomposition temperature, decomposing into lithium oxide and carbon dioxide at approximately 700°C. This allows lithium carbonate to form lithium-containing phosphates at relatively high temperatures, meaning that the reaction crystallization temperature for lithium-containing phosphate formation is wide, which is more conducive to the formation of primary particles with a particle size of 150nm-2000nm. In particular, by controlling the mass percentage of lithium carbonate at 80%-90%, the proportion of primary particles with a specific particle size can be adjusted, ensuring that the proportion of primary particles with a particle size of 150nm-2000nm is not less than 80%, thus giving the phosphate-based cathode material an appropriate particle size distribution.

[0067] In some embodiments, in step S10, the lithium source further includes a modified lithium source, which includes at least one of lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxide.

[0068] The purpose of adding a modified lithium source in this application is to finely control the particle size of primary particles in phosphate-based cathode materials. For example, lithium dihydrogen phosphate has a low decomposition temperature, approximately 200℃-400℃, which allows for the formation of lithium-containing phosphates at lower temperatures, thereby promoting the formation of primary particles with a particle size <50nm. Therefore, by adding a modified lithium source, it is possible to promote the formation of phosphate-based cathode materials with a more suitable particle size distribution, thereby improving the energy density, cycle performance, and other electrochemical performance of the battery.

[0069] In some embodiments, in step S10, the iron source includes ferric phosphate, and the mass percentage of ferric phosphate in the iron source is 80%-90%.

[0070] As an example, the mass percentage of iron phosphate in the iron source can be typical but not limiting values ​​such as 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%.

[0071] The high decomposition temperature of iron phosphate allows for a wider reaction crystallization temperature range when iron phosphate and lithium carbonate react to form lithium-containing phosphates, thus promoting the formation of primary particles with a particle size of 150nm-2000nm. Furthermore, controlling the mass percentage of iron phosphate to 80%-90% ensures that the proportion of primary particles of a specific size is not less than 80%, thereby obtaining a phosphate-based cathode material with a suitable particle size distribution.

[0072] In some embodiments, in step S10, the iron source further includes a modified iron source, which includes at least one of iron-based metal salts and iron-based oxides.

[0073] As an example, iron-based metal salts include at least one of ferrous sulfate, ferrous nitrate, and ferrous oxalate.

[0074] As an example, iron-based oxides include at least one of ferric oxide, iron(II) oxide, and ferrous oxide.

[0075] The purpose of adding modified iron sources in this application is to finely control the particle size of primary particles in phosphate-based cathode materials. For example, ferrous oxalate has a low decomposition temperature, decomposing into ferrous oxide, carbon monoxide, and carbon dioxide at 200℃-300℃. This means that ferrous oxalate can generate lithium-containing phosphate at low temperatures, forming primary particles with a particle size <50nm. Conversely, ferric oxide has a high reduction temperature, decomposing into ferrous oxide and carbon monoxide at 500℃-600℃. Utilizing its moderate decomposition temperature, ferrous oxide can form primary particles with a particle size of approximately 100nm when reacting with a lithium source such as lithium phosphate. Therefore, by adding the aforementioned modified iron sources, it is possible to promote the formation of phosphate-based cathode materials with a more suitable particle size distribution, thereby improving the energy density, cycle performance, and other electrochemical performance of the battery.

[0076] In some embodiments, in step S10, the molar ratio of iron in the iron source to phosphorus in the phosphorus source in the raw material composition is Fe:P = (0.96-0.98):1.

[0077] Within the aforementioned molar ratio of iron to phosphorus, uniform growth of lithium phosphate grains is promoted, the formation of inactive impurity phases is reduced, and the purity of lithium phosphate is improved. Furthermore, a slight deficiency of iron introduces trace lithium vacancies into the crystal lattice, forming ion channels, accelerating lithium-ion diffusion, and improving the rate performance of the cathode material. Simultaneously, ferrous ions are more stable in a phosphorus-rich environment, reducing the formation of iron ions due to oxidation during synthesis and mitigating the risk of capacity loss.

[0078] In some embodiments, in step S10, the molar ratio of lithium in the lithium source to iron in the iron source in the raw material composition is Li:Fe = (1.00-1.03):1.

[0079] Within the aforementioned range, ensuring sufficient lithium source in the raw material components not only helps reduce the formation of lithium defects but also helps maintain an alkaline synthesis environment and reduce the dissolution of ferrous ions, thereby obtaining lithium phosphate with high purity and uniform grain size.

[0080] In some embodiments, in step S10, the phosphorus source includes at least one of phosphoric acid and ammonium dihydrogen phosphate.

[0081] Of course, if the iron or lithium source contains phosphorus, such as lithium phosphate or iron phosphate, and the phosphorus content meets the stoichiometric requirements for lithium phosphate, then there is no need to add an additional phosphorus source.

[0082] In some embodiments, in step S10, the doping source includes at least one of a titanium source, a vanadium source, a magnesium source, and an aluminum source.

[0083] By adding doping sources, phosphate-based cathode materials can contain doping elements such as vanadium, titanium, magnesium, and aluminum, making them suitable for various applications such as power batteries and energy storage batteries.

[0084] In some embodiments, in step S10, the mass percentage of the dopant element in the dopant source relative to the theoretical yield of the phosphate-based cathode material is 0.4%-1%.

[0085] The doping source includes the oxide or organic compound corresponding to the doping element. For example, the titanium source includes at least one of titanium dioxide, tetrabutyl titanate, etc.; the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum nitrate; and the vanadium source includes at least one of ammonium metavanadate, vanadium nitrate, and vanadium pentoxide.

[0086] Adding doping sources allows phosphate-based cathode materials to contain doping elements such as vanadium, titanium, magnesium, and aluminum. In application, the amount of doping source added can be controlled, thereby controlling the total amount of doping elements to be equivalent to the mass content in the prepared phosphate-based cathode material of 0.4%-1%, or 4000ppm-10000ppm, as mentioned above.

[0087] In some embodiments, in step S20, the carbon source includes at least one of glucose, sucrose, and white sugar.

[0088] In some embodiments, in step S20, the amount of carbon source added is 15%-25% by mass relative to the theoretical yield of the phosphate-based cathode material.

[0089] These carbon sources can form carbon materials during the sintering process and coat the surface of the lithium phosphate core to form a carbon shell.

[0090] In some embodiments, in step S20, the iron-based dispersant comprises an iron-polyamine complex. As an example, the iron-based dispersant comprises at least one of tri(ethylenediamine)fer(III) nitrate ([Fe(en)3](NO3)3), triethanolaminefer(III) nitrate ([Fe(TEA)](NO3)3), triethylenetetraminefer(III) nitrate ([Fe(TETA)](NO3)3), and ethylenediaminetetraacetic acidfer(III) nitrate ([Fe(EDTA)](NO3)3).

[0091] The ligands contained in these iron-based dispersants can form complexes with iron ions. These complexes, on the one hand, utilize their own steric hindrance or charge repulsion to adjust the particle size of primary particles; on the other hand, they can form lithium iron phosphate crystal carriers (i.e., lithium phosphate) with lithium sources during subsequent sintering, thereby improving the reactivity of phosphate-based cathode materials; furthermore, the ligands contained in the complexes can also act as carbon sources, forming carbon materials that coat the surface of the lithium phosphate core during sintering, improving the dispersibility of the resulting composite particles and reducing floating carbon.

[0092] In some embodiments, in step S20, the amount of iron-based dispersant added is 0.5%-2% by mass relative to the theoretical yield of phosphate-based cathode material.

[0093] For example, the amount of iron-based dispersant added as a percentage by mass relative to the theoretical yield of phosphate-based cathode materials can be a typical but not limiting value among 0.5%, 1%, 1.5%, 1.8%, and 2%.

[0094] In some embodiments, step S20, the mixing process includes a grinding process and a spray drying process performed sequentially.

[0095] Grinding can use mechanical force (such as ball milling and sand milling) to break up the initial agglomerated particles of raw materials such as iron, lithium, and phosphorus sources, dispersing them into submicron or nano-sized particles, increasing the contact area between raw materials, and promoting the uniform distribution of each raw material component at the microscale.

[0096] Spraying allows the ground slurry to be dispersed into droplets, and then the solvent is rapidly evaporated in a hot air stream, causing the raw material mixture to form spherical precursor particles inside the droplets, thus making the mixture particles spherical.

[0097] In some embodiments, in step S20, the mixing process includes sand milling, wherein the zirconium balls used for sand milling have a size of 0.8 μm.

[0098] The grinding process can be carried out using a sand milling process, for example, using zircon balls with a diameter of 0.8 μm as the grinding medium and an aqueous ethanol solution (the volume ratio of anhydrous ethanol to water is 7-9:3-1) as the dispersion solvent.

[0099] In some embodiments, in step S20, the mixing process includes spray drying, and the inlet air temperature of the spray drying is 150°C-200°C, and the outlet air temperature is 60°C-100°C.

[0100] For example, the inlet air temperature can be a typical but non-limiting value such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., and the outlet air temperature can be a typical but non-limiting value such as 60°C, 70°C, 80°C, 90°C, 100°C, etc.

[0101] By controlling the inlet and outlet air temperatures within the above range, the particle size and morphological regularity of the mixture can be effectively regulated, resulting in a mixture with high sphericity and moderate particle size.

[0102] In some embodiments, in step S20, the particle size of the mixture is 330nm-370nm.

[0103] For example, the particle size of the mixture can be typical but not limiting values ​​such as 330nm, 340nm, 350nm, 360nm, and 370nm.

[0104] In some embodiments, step S30 includes a first sintering process, a second sintering process, and a third sintering process performed sequentially. The first sintering process includes sintering at 180°C-200°C for 1-2 hours at a heating rate of 1°C / min-3°C / min. The second sintering process includes sintering at 400°C-500°C for 2-3 hours at a heating rate of 2°C / min-4°C / min. The third sintering process includes sintering at 700°C-780°C for 8-13 hours at a heating rate of 3°C / min-5°C / min.

[0105] Specifically, the sintering process is carried out under a protective atmosphere, such as at least one of nitrogen, argon, and helium.

[0106] The technical solution of this application adopts a staged sintering method, which helps to optimize the particle size, distribution, and morphological regularity of the primary particles. Specifically:

[0107] The first sintering process involves a low heating rate and a low holding temperature; this stage can be understood as low-temperature preheating. Slow heating prevents the iron, lithium, and phosphoric acid sources from experiencing sudden temperature changes that could lead to violent localized reactions, suppressing the explosive growth of initial crystal nuclei and forming uniform, fine initial crystal nuclei. The low-temperature holding conditions promote solid-state diffusion between raw materials, such as the initial combination of lithium ions, ferrous ions, and phosphate ions, reducing the risk of large particle agglomeration.

[0108] The heating rate of the second sintering process is slightly increased, and the holding temperature is significantly increased. Under these conditions, the initial crystal nuclei can grow at a controllable rate, thus gradually increasing the particle size. The higher holding temperature and the appropriate holding time can reduce the dispersion of particle size distribution and make the grain size more uniform.

[0109] The holding temperature and holding time of the third sintering process are significantly increased. During this process, atomic diffusion can be accelerated, grain interface fusion can be promoted, and the balance between grain growth rate and thermal stability can be achieved. Ultimately, a phosphate-based cathode material with moderate particle size distribution, i.e., the proportion of primary particles with a particle size of 150nm-2000nm is not less than 80%, is obtained.

[0110] Thirdly, this application provides a lithium-ion battery, including a positive electrode and a negative electrode. The positive electrode includes the phosphate-based positive electrode material provided in the first aspect or the phosphate-based positive electrode material prepared by the preparation method provided in the second aspect.

[0111] The lithium-ion battery provided in the third aspect of this application contains the phosphate-based cathode material of this application, and the phosphate-based cathode material has the characteristics of moderate particle size distribution, high ionic conductivity, and high electronic conductivity, thereby improving the energy density, rate performance, cycle life and other electrochemical performance of the lithium-ion battery.

[0112] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector, wherein the positive active layer includes the phosphate-based positive electrode material described in any of the above embodiments. In one embodiment of this application, the positive current collector includes, but is not limited to, at least one of aluminum foil, carbon-coated aluminum foil, iron foil, tin foil, zinc foil, nickel foil, titanium foil, and manganese foil. In one embodiment of this application, the positive current collector may be aluminum foil.

[0113] In some embodiments, the preparation of the positive electrode active layer includes the following steps: mixing the above-mentioned phosphate-based positive electrode material, conductive agent and binder to form an electrode slurry, coating the electrode slurry onto the current collector, and preparing a positive electrode sheet by drying, rolling, die cutting and other steps.

[0114] In some embodiments, the mass percentage of phosphate-based cathode material in the cathode active layer is 80%-95%. Specifically, the mass percentage of phosphate-based cathode material in the cathode active material layer can be 80%, 85%, 88%, 90%, 95%, etc.

[0115] In some embodiments, the binder content in the positive electrode active layer is 2wt%-5wt%. In specific embodiments, the binder content can be a typical but not limited content such as 2wt%, 3wt%, 4wt%, 5wt%.

[0116] In some embodiments, the adhesive includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethylcellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.

[0117] In some embodiments, the content of the conductive agent in the positive electrode active material layer is 1wt%-5wt%. In specific embodiments, the content of the conductive agent can be a typical but not limited content such as 3wt%, 4wt%, or 5wt%.

[0118] In some embodiments, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes.

[0119] This application does not specifically limit the negative electrode, electrolyte, separator, etc. in the lithium-ion battery of the embodiments, and can be applied to any battery system.

[0120] In some embodiments, the negative electrode active material of the lithium-ion battery includes, but is not limited to, carbon materials such as graphite, soft carbon (e.g., coke), and hard carbon, or nitrides, tin-based oxides, tin alloys, and nano-anode materials. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.

[0121] In some embodiments, the steps for preparing the negative electrode sheet include: preparing a negative electrode mixed slurry by mixing the negative electrode active material with conductive agents such as conductive carbon black, binders such as carboxymethyl cellulose and styrene-butadiene rubber, and solvents such as water in a mass ratio of (80-99):(1-5):(2-10):100, degassing under vacuum, discharging the material, coating it on a coating machine, and obtaining the negative electrode sheet after rolling, slitting, and die-cutting.

[0122] In some embodiments, the membrane is capable of blocking electrons while allowing ions to pass through. Exemplary examples include, but are not limited to, at least one material selected from polypropylene fibers, polyacrylonitrile fibers, polyvinyl formal fibers, poly(ethylene glycol terephthalate), polyethylene terephthalate, polyamide fibers, and poly(p-phenylene terephthalamide).

[0123] In some embodiments, the electrolyte comprises at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], and Li[(FSO2)2N].

[0124] In some embodiments, a lithium-ion battery can be a rechargeable battery, which refers to a lithium-ion battery that can be recharged after discharge to activate the active materials and continue to be used. As an example, a lithium-ion battery includes at least one of a battery cell, a battery module, and a battery pack.

[0125] To enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant improvement in the performance of the phosphate-based cathode material and its preparation method in the embodiments of this application, the above technical solutions are illustrated below through multiple embodiments.

[0126] Example 1

[0127] This embodiment provides a phosphate-based cathode material and its preparation method.

[0128] A phosphate-based cathode material includes several composite particles. Each composite particle comprises a lithium-containing phosphate core and a carbon shell coating the outer surface of the lithium-containing phosphate core. In the composite particles, the proportion of primary particles with a diameter of 150 nm to 500 nm is not less than 80%.

[0129] A method for preparing a phosphoric acid-based cathode material includes the following steps:

[0130] Step 1: Provide lithium source, iron source, carbon source (glucose), titanium source (tetrabutyl titanate) and iron-based dispersant ([Fe(en)3](NO3)3).

[0131] The lithium source includes lithium carbonate and modified lithium source (lithium dihydrogen phosphate) in a mass ratio of 8:2, and the iron source includes iron phosphate and modified iron source (ferric oxide) in a mass ratio of 8:2.

[0132] The molar ratio of iron in the iron source to phosphorus in the phosphorus source is Fe:P = 0.98:1; the molar ratio of lithium in the lithium source to iron in the iron source is Li:Fe = 1.03:1; the mass percentage of titanium in the titanium source relative to the theoretical yield of the phosphate-based cathode material is 0.8% (8000 ppm of titanium is added per kilogram of phosphate-based cathode material); the mass percentage of carbon source added relative to the theoretical yield of the phosphate-based cathode material is 19.14% (30.2 g of carbon source is added per kilogram of lithium-containing phosphate); and the mass percentage of iron-based dispersant added relative to the theoretical yield of the phosphate-based cathode material is 1%.

[0133] Step 2: Place the lithium source, iron source, carbon source, titanium source and iron-based dispersant in a sand mill, use zirconium balls with a diameter of 0.8 μm as the grinding medium, and use anhydrous ethanol and water with a volume ratio of 8:2 as the solvent for grinding treatment until the particle size is 350 nm. Then, spray dry the mixture with an inlet air temperature of 200 °C and an outlet air temperature of 90 °C to obtain the mixture.

[0134] Step 3: Place the mixture in a tube furnace and sinter under high-purity nitrogen protection. The sintering process includes a first sintering process, a second sintering process, and a third sintering process performed sequentially. First sintering process: heat to 180℃ at a heating rate of 3℃ / min and sinter for 1 hour; Second sintering process: heat to 400℃ at a heating rate of 2℃ / min and sinter for 2 hours; Third sintering process: heat to 780℃ at a heating rate of 3℃ / min and sinter for 10 hours. Finally, cool to room temperature to obtain the phosphate-based cathode material.

[0135] Example 2

[0136] This embodiment provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is that:

[0137] The lithium source includes lithium carbonate in a mass ratio of 8:2 and a modified lithium source, which is lithium phosphate.

[0138] Example 3

[0139] This embodiment provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is that:

[0140] The lithium source includes lithium carbonate in a mass ratio of 8:2 and a modified lithium source, which is lithium hydroxide.

[0141] Example 4

[0142] This embodiment provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is that:

[0143] The iron source includes iron phosphate in a mass ratio of 8:2 and a modified iron source, which is ferrous oxalate.

[0144] Example 5

[0145] This embodiment provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is that:

[0146] The lithium source includes lithium carbonate and modified lithium source (lithium dihydrogen phosphate) in a mass ratio of 9:1, and the iron source includes iron phosphate and modified iron source (ferric oxide) in a mass ratio of 9:1.

[0147] Example 6

[0148] This embodiment provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is the amount of iron-based dispersant added, as detailed below:

[0149] The amount of iron-based dispersant added is 2% by mass relative to the theoretical yield of phosphate-based cathode materials.

[0150] Comparative Example 1

[0151] This comparative example provides a phosphate-based cathode material and its preparation method. The only difference between this material and Example 1 is that no iron-based dispersant was added.

[0152] Comparative Example 2

[0153] This comparative example provides a phosphate-based cathode material and its preparation method. The only difference between this example and Example 1 is that the lithium source comprises lithium phosphate and lithium dihydrogen phosphate in a mass ratio of 8:2.

[0154] Comparative Example 3

[0155] This comparative example provides a phosphate-based cathode material and its preparation method. The only difference between this example and Example 1 is that the iron source comprises ferrous oxalate and ferric phosphate in an 8:2 ratio.

[0156] The physicochemical properties of the phosphate-based cathode materials prepared in the above embodiments and comparative examples are shown in Table 1 below.

[0157] Table 1

[0158]

[0159] In Table 1, [150nm-2000nm] indicates that the particle size of a primary particle satisfies the condition of being greater than or equal to 150nm and less than or equal to 2000nm.

[0160] As shown in Table 1, the embodiments of this application employ specific lithium sources, specific iron sources, and iron-based dispersants as reaction raw materials. For example, the lithium source includes lithium carbonate with a mass percentage of not less than 80%, and the iron source includes iron phosphate with a mass percentage of not less than 80%. This allows the iron and lithium sources to participate in the formation of lithium-containing phosphates at high temperatures, thereby effectively controlling their nucleation and growth processes and optimizing the particle size distribution of the phosphate-based cathode material. For example, in Examples 1-6, the proportion of primary particles located in the 150nm-2000nm range reaches over 90%.

[0161] Methods for determining the average particle size of primary particles in phosphate-based cathode materials:

[0162] The phosphate-based cathode materials in each of the above embodiments were analyzed by scanning electron microscopy (SEM). The particle size characteristics of the phosphate-based cathode materials were measured based on the SEM images, and the average particle size of the primary particles in each embodiment was statistically calculated based on the SEM data. Simultaneously, the particle size of the primary particles was statistically analyzed, and the proportion of particles with a size in the 150nm-2000nm range was calculated.

[0163] The morphology of the phosphate-based cathode material prepared in Example 1 was observed by scanning electron microscopy (SEM), and the SEM images are shown below. Figure 1As shown, in the prepared phosphate-based cathode material, most of the primary particles are spherical particles with a diameter of 150 nm to 500 nm.

[0164] The morphology of the phosphate-based cathode material provided in Comparative Example 1 was observed using a scanning electron microscope (SEM), and the SEM images are shown below. Figure 2 As shown. (Through) Figure 1 and Figure 2 The comparison shows that: Figure 1 The particles are smooth, round, and evenly distributed. Figure 2 The particles have residual carbon on their surface, resulting in poor carbon coating and uneven particle distribution.

[0165] Example of a lithium-ion battery:

[0166] The phosphate-based cathode materials prepared in the above embodiments and comparative examples are applied to lithium-ion batteries. The specific preparation steps are as follows:

[0167] Positive electrode sheet: Under the same conditions, positive electrode active material, SP (conductive carbon black), PVDF (polyvinylidene fluoride) and NMP (N-methylpyrrolidone) are mixed in a mass ratio of 95:2:3:100 and stirred in a closed mixer for 2 hours to obtain a uniform positive electrode slurry. The prepared positive electrode slurry is coated onto aluminum foil, evenly smoothed with a scraper, dried at 130°C, and then rolled to obtain a positive electrode sheet. The positive electrode active material is the phosphate-based positive electrode material provided in the above embodiment and the phosphate-based positive electrode material provided in the comparative example.

[0168] Negative electrode: Graphite negative electrode.

[0169] Electrolyte: 1.0 mol / L LiPF6 solution is used as the electrolyte. The solvent of the electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) in a volume ratio of 1:1:1.

[0170] Separator: Celgard 2400 microporous membrane.

[0171] Lithium-ion battery assembly: The positive electrode, separator, electrolyte, and negative electrode are assembled into a button cell in an inert atmosphere glove box.

[0172] The coin cells containing the positive electrode materials provided in Examples 1-6 are respectively referred to as Examples S1-S6, and the coin cells containing the positive electrode materials provided in Comparative Examples 1-3 are referred to as Comparative Examples DS1-DS3.

[0173] Electrochemical performance testing:

[0174] (1) 0.1C discharge capacity

[0175] After the battery formation is completed, at room temperature of 25°C, the charge and discharge voltage window is controlled between 2.0 and 3.75V. The battery is charged at 0.1C (cutoff current 0.025C) and discharged at 0.1C to obtain a discharge capacity of 0.1C.

[0176] (2) 1C discharge capacity

[0177] After the battery formation is completed, at room temperature of 25°C, the charge and discharge voltage window is controlled between 2.0 and 3.75V. The battery is charged at 1C (cutoff current 0.025C) and discharged at 1C to obtain a 1C discharge capacity.

[0178] (3) Energy efficiency of 0.5p per 100 cycles

[0179] A. Charging Process

[0180] Charging: Charge at a constant current of 0.5C to 4.2V, then switch to constant voltage charging until the current is ≤0.05C, and let stand for 1 hour.

[0181] Stand still: Let stand for 2 hours at 25℃ to ensure the battery condition is stable.

[0182] B. Loop Testing Process

[0183] Number of cycles: 100 to 1000.

[0184] Single loop operation:

[0185] Discharge: Discharge at a constant current of 0.5C to 50% SOC (i.e., discharge from 100% SOC to 50% SOC).

[0186] Let stand: 10-30 minutes apart (to eliminate polarization effect).

[0187] Charging: Charge at a constant current of 0.5C to 100% SOC (cutoff voltage 4.2V), then switch to constant voltage charging until the current is ≤0.05C.

[0188] Let stand: Let stand for another 10 to 30 minutes, and record data such as voltage, temperature, and capacity.

[0189] The electrochemical test results are shown in Table 2 below.

[0190] Table 2

[0191]

[0192] As can be seen from Table 1-2:

[0193] Compared to comparative examples DS1-DS3, embodiments S1-S6 of this application have significant advantages in electrochemical performance, specifically higher discharge capacity and better cycle performance.

[0194] Combining Example S1 and Comparative Example DS1, it can be seen that the introduction of iron-based dispersants plays an important role in regulating the particle size of primary particles in lithium phosphate. Through the formation of complexes between the ligand polyamine and iron ions, the dispersant utilizes its own steric hindrance or charge repulsion to inhibit the excessive growth of primary particles, reducing the average particle size of primary particles from 500 nm to 260 nm, and increasing the proportion of primary particles in the 120 nm-2000 nm range from 70% to 99%. Electrochemical performance data indicate that optimizing the particle size distribution of lithium phosphate helps improve battery capacity and energy efficiency.

[0195] Combining Example S1 and Comparative Examples DS2-DS3, it can be seen that the choice of lithium source or iron source significantly affects the sintering kinetics of lithium phosphate, thereby affecting the particle size distribution of its primary particles, i.e., the average particle size and the proportion of primary particles. For example, in Comparative Example 2, the proportion of primary particles in the 150nm-2000nm range of lithium phosphate is only 30%, exhibiting a wide particle size distribution. This wide particle size distribution is not conducive to efficient stacking between particles, and thus not conducive to improving the energy density and cycle performance of the battery.

[0196] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A phosphate-based cathode material, characterized in that, It includes several composite particles, wherein the composite particles include a lithium phosphate core and a carbon shell covering the outer surface of the lithium phosphate core; In the composite particles, the proportion of primary particles with a diameter of 150nm-2000nm is not less than 80%; The raw materials for the phosphate-based cathode material include a lithium source, an iron source, and an iron-based dispersant. The lithium source includes lithium carbonate, and the mass percentage of lithium carbonate in the lithium source is not less than 80%; the iron source includes iron phosphate, and the mass percentage of iron phosphate in the iron source is not less than 80%; the iron-based dispersant includes an iron-polyamine complex.

2. The phosphate-based cathode material as described in claim 1, characterized in that, In the composite particles, the proportion of primary particles with a particle size of 150nm-500nm is not less than 80%.

3. The phosphate-based cathode material as described in claim 1 or 2, characterized in that, The molecular formula of the lithium phosphate core is LiFe. 1-x M x PO4, wherein M includes at least one of Ti, Mg, Al, and V, 0 ≤ x ≤ 0.1; and / or, The phosphate-based cathode material has a spherical particle morphology; and / or, In the phosphate-based cathode material, the carbon shell layer accounts for 1%-10% of the total mass; and / or, The carbon shell includes the carbonized products of the ligands in the iron-polyamine complex; and / or The 0.1C discharge capacity of the phosphate-based cathode material is greater than or equal to 158 mAh / g; and / or, The phosphate-based cathode material has a 1C discharge capacity greater than or equal to 148 mAh / g.

4. A method for preparing a phosphate-based cathode material, characterized in that, Includes the following steps: The raw material components, including lithium source, iron source, phosphorus source and doping source, are obtained according to the stoichiometric ratio of lithium phosphate. The lithium source includes lithium carbonate and the iron source includes iron phosphate. The raw material components, carbon source, iron-based dispersant, and solvent are mixed to obtain a mixture. Wherein, the lithium carbonate accounts for no less than 80% of the mass of the lithium source; the iron phosphate accounts for no less than 80% of the mass of the iron source; and the iron-based dispersant includes an iron-polyamine complex. The mixture is sintered to form a phosphate-based cathode material containing a lithium phosphate core and a carbon shell covering the outer surface of the lithium phosphate core.

5. The method for preparing the phosphate-based cathode material as described in claim 4, characterized in that, The sintering process includes a first sintering process, a second sintering process, and a third sintering process performed sequentially. The first sintering process includes sintering at 180℃-200℃ for 1h-2h at a heating rate of 1℃ / min-3℃ / min. The second sintering process includes sintering at 400℃-500℃ for 2h-3h at a heating rate of 2℃ / min-4℃ / min. The third sintering process includes sintering at 700℃-780℃ for 8h-13h at a heating rate of 3℃ / min-5℃ / min.

6. The method for preparing the phosphate-based cathode material as described in claim 4, characterized in that, The lithium carbonate comprises 80%-90% by mass in the lithium source; and / or, The lithium source also includes a modified lithium source, which includes at least one of lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxide.

7. The method for preparing the phosphate-based cathode material as described in claim 4, characterized in that, The iron phosphate comprises 80%-90% by mass in the iron source; and / or, The iron source also includes a modified iron source, which includes at least one of iron-based metal salts and iron-based oxides.

8. The method for preparing the phosphate-based cathode material according to any one of claims 4 to 7, characterized in that, The particle size of the mixture is 330nm-370nm; and / or, The mixing process includes sand milling, where the zirconium balls used in the sand milling have a size of 0.8 μm; and / or, The mixing process includes spray drying, wherein the inlet air temperature of the spray dryer is 150℃-200℃ and the outlet air temperature is 60℃-100℃; and / or, The carbon source includes at least one selected from glucose, sucrose, and white sugar; and / or, The iron-based dispersant includes at least one of [Fe(en)3](NO3)3, [Fe(TEA)](NO3)3, [Fe(TETA)](NO3)3, and [Fe(EDTA)](NO3); and / or The doping source includes at least one of titanium, vanadium, magnesium, and aluminum sources.

9. The method for preparing the phosphate-based cathode material according to any one of claims 4 to 7, characterized in that, The amount of the iron-based dispersant added is 0.5%-2% by mass relative to the theoretical yield of the phosphate-based cathode material; and / or, The amount of the dopant source added is 0.4%-1% by mass relative to the theoretical yield of the phosphate-based cathode material; and / or, The amount of carbon source added is 15%-25% by mass relative to the theoretical yield of the phosphate-based cathode material.

10. A lithium-ion battery, comprising a positive electrode and a negative electrode, characterized in that, The positive electrode sheet includes the phosphate-based positive electrode material as described in any one of claims 1-3 or the phosphate-based positive electrode material prepared by the preparation method as described in any one of claims 4-9.

Citation Information

Patent Citations

  • Lithium iron phosphate-based precursor, positive electrode material and preparation method and application of lithium iron phosphate-based precursor and positive electrode material

    CN117682494A

  • Preparation method of positive electrode material and energy storage battery

    CN119008910A